Incidence and Antiseizure Medications of Post-stroke Epilepsy in Umbria: A Population-Based Study Using Healthcare Administrative Databases - Costa, Cinzia; Nardi Cesarini, Elena; Eusebi, Paolo; Franchini, David; Casucci, Paola; De Giorgi, Marcello; Calvello, Carmen; Romoli, Michele; Parnetti, Lucilla; Calabresi, Paolo (Frontiers in Neurology, 2022)
Introduction: Post-stroke epilepsy (PSE) requires long-term treatment with antiseizure medications (ASMs). However, epidemiology of PSE and long-term compliance with ASM in this population are still unclear. Here we report, through population-level healthcare administrative data, incidence, risk factors, ASM choice, and ASM switch over long-term follow-up. Materials and Methods: This is a population-based retrospective study using Umbria healthcare administrative database. Population consisted of all patients with acute stroke, either ischaemic or hemorrhagic, between 2013 and 2018. ICD-9-CM codes were implemented to identify people with stroke, while PSE was adjudicated according to previously validated algorithm, such as EEG and ≥1 ASM 7 days after stroke. Results: Overall, among 11,093 incident cases of acute stroke (75.9% ischemic), 275 subjects presented PSE, for a cumulative incidence of 2.5%. Patients with PSE were younger (64 vs. 76 years), more frequently presented with hemorrhagic stroke, and had longer hospital stay (15.5 vs. 11.2 days) compared with patients without PSE. Multivariable Cox proportional hazards models confirmed that PSE associated with hemorrhagic stroke, younger age, and longer duration of hospital stay. Levetiracetam was the most prescribed ASM (55.3%), followed by valproate and oxcarbazepine. Almost 30% of patients prescribed with these ASMs switched treatment during follow-up, mostly toward non-enzyme-inducing ASMs. About 12% of patients was prescribed ASM polytherapy over follow-up. Conclusions: Post-stroke epilepsy is associated with hemorrhagic stroke, younger age, and longer hospital stay. First ASM is switched every one in three patients, suggesting the need for treatment tailoring in line with secondary prevention.